MENGINTEGRASIKAN KARAKTER RELIGIUS PADA PEMBELAJARAN KIMIA DALAM MENINGKATKAN PEMAHAMAN MATERI SISTEM PERIODIK UNSUR - Viqhi Aswie (JENTRE, 2023)
The understanding of class X IPS MAN 1 Kota Sukabumi for the 2021/2022 academic year, which in the basic competency assessment of 3.3, namely related to material on the periodic system of elements, did not achieve 50% passing the Minimum Completeness Criteria (KKM ≥ 75). In addition, the low value of cognitive knowledge is still directly proportional to students' understanding of religious character values ​​in chemistry learning. In fact, the cognitive and character realms are important things to be achieved in the curriculum. Thus, learning chemistry integrated with religious character certainly has the opportunity to be applied. This study aims to increase students' understanding of MAN 1 Kota Sukabumi regarding the the periodic system of elements subject through the application of integrated chemistryl learning with religious character in chemistry learning through the use of the ptable.com site learning media. approach to the results of the pre-test and post-test on the Periodic System of Elements material given to the research sample. The population of this study were students of class X. IPS MAN 1 Kota Sukabumi by taking 2 study groups in class X. IPS 4 and X IPS 6 as a sample. After the data was obtained, a comparative analysis was then carried out by comparing the findings with some relevant literature. The results of this study showed that 80.20% of students understood the periodic system of elements using the ptable.com site and 91.50% of students were interested in implementing integrated chemistry learning with verses of the Qur’an.